A COMPARATIVE STUDY ON LATTICE DYNAMICS AND SPECIFIC HEAT OF ANTIFLUORITE SUPERIONIC OXIDES Li2O, Na2O and K2O - AnupamDeepSharma, PankajKumar; M. M. Sinha (International Journal of Research Science and Management, 2016)
Superionic oxideslike Li2O, Na2O and K2O are the materials of technological interest, exhibits high ionic conductivity while in solid condition and belongs to the class of fast ion conduction, which allow macroscopic movement of ions through their structure. These superionic conductors find several technological applications. These applications range from miniature light weight high power density lithium ion batteries for heart pacemakers, mobile phones, laptops computers, etc. to high capacity energy storage devices for next generation. Therefore knowledge of the thermal properties of these materials is most significant. Hence in the present study we have studied phonon dispersion relation, phonon density of states and specific heat of Li2O, Na2O and K2O in antifluorite structure by applying lattice dynamical theoretical model. The calculated results are interpreted with existing experimental or theoretical results.